A Bimodal Biometric Technique Based Enhanced Real-Time ATM System with Intelligence Security Measures - Vithya.T; Parthiban S (International Journal of Computer Sciences and Engineering, 2014)
In this paper, a real-time embedded multimodal biometric recognition system for authentication on Automated teller machine is being developed. The system is implemented on an embedded platform and equipped with novel multimodal recognition algorithms, so this system is an intelligent security system; it is developed based on a teller machine concept. Wherein, the transaction is successful, If and only if the biometric used is matched and GSM technology is used.